Pancasila dan Pendidikan Agama Islam sebagai Landasan Filosofis dan Yuridis: Rekonstruksi Hukum Tata Negara melalui Islamic Sociological Jurisprudence Theory - Ahmad Muhamad Mustain Nasoha; Giral Ilham Bagus Pramudiansyah; Faa’iz Zainul Muttaqin; Muhammad Nadhif Mirzaq (International Forum of Researchers and Lecturers, 2026)
. This study aims to reconstruct Indonesia’s constitutional law by positioning Pancasila and Islamic Religious Education as its philosophical and juridical foundations through the Islamic Sociological Jurisprudence Theory developed by Ahmad Muhammad Mustain Nasoha. The background of this research is the gap between positive legal norms and socio-religious values existing in society, thus requiring an integrative approach that connects normative and sociological dimensions within the legal system. This study employs a qualitative method with normative and sociological approaches through library research involving various legal sources, literature, and relevant theoretical perspectives. The findings indicate that the values of Pancasila are in harmony with Islamic principles, particularly in terms of justice, public welfare (maslahah), and social balance. Islamic Religious Education plays a significant role in internalizing these values into societal life and state practice. Therefore, the reconstruction of constitutional law is directed toward the development of a legal system that is not merely formal-legalistic, but also responsive to social realities, contextually grounded in national cultural values, and oriented toward comprehensive societal welfare.